2016
DOI: 10.1080/00325481.2016.1173515
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and acceptability of oxcarbazepine vs. carbamazepine with betahistine mesilate tablets in treating vestibular paroxysmia: a retrospective review

Abstract: These results indicated that using BMT as an augmentation for CBZ or OXC might be a good choice in treating VP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…In a randomized controlled clinical trial, OXA treatment reduced the number of days with at least one vertigo attack by one-third, and the average number of attacks almost to half the numbers under placebo. This is consistent with open-label studies and clinical experience with OXA and other sodium channel blockers in VP [ 1 , 14 ]. This is also consistent with the benefit to patients with other neurovascular compression syndromes, i.e., trigeminal neuralgia and hemifacial spasm, from CBZ or OXA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In a randomized controlled clinical trial, OXA treatment reduced the number of days with at least one vertigo attack by one-third, and the average number of attacks almost to half the numbers under placebo. This is consistent with open-label studies and clinical experience with OXA and other sodium channel blockers in VP [ 1 , 14 ]. This is also consistent with the benefit to patients with other neurovascular compression syndromes, i.e., trigeminal neuralgia and hemifacial spasm, from CBZ or OXA.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of treatment, in the initial studies, surgical decompression was recommended [ 12 , 13 ]. Nowadays, the treatment of choice for VP, as with the other cranial nerve NVCC syndromes, is the use of carbamazepine (CBZ) or OXA, also based on two retrospective studies [ 1 , 14 ]. Both showed a good effect of CBZ and oxcarbazepine (OXA) (for review see [ 15 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Our retrospective review found that the response rates in both the CBZ+BMT group and the OXC+BMT group were higher compared to the CBZ-alone group, which indicated that BMT could provide effective augmentation for CBZ and OXC in treating VP. 13 In our previous study, we also found that CBZ+BMT and OXC+BMT had similar efficacy and acceptability. 13 But this finding needs to be assessed in further research, for the following two reasons: 1) our previous study was not a randomized controlled trial; and 2) the doses of CBZ, OXC, and BMT are different in different patients.…”
Section: Introductionmentioning
confidence: 73%
“… 13 In our previous study, we also found that CBZ+BMT and OXC+BMT had similar efficacy and acceptability. 13 But this finding needs to be assessed in further research, for the following two reasons: 1) our previous study was not a randomized controlled trial; and 2) the doses of CBZ, OXC, and BMT are different in different patients. Therefore, this randomized controlled trial was conducted to evaluate whether CBZ+BMT and OXC+BMT had similar efficacy and acceptability in treating VP, and to investigate whether the synergistic effect could be increased along with the increased dose of BMT.…”
Section: Introductionmentioning
confidence: 73%
“…Yi et al, compared carbamazepine, carbamazepine plus betahistine mesilate and oxcarbazepine plus betahistine mesilate in treating vestibular paroxysmia in a retrospective review. 39 After 12 weeks' treatment, the carbamazepine plus betahistine mesilate group had a greater reduction in the frequency of vertigo, vertigo duration and vertigo score than the other two groups. The oxcarbazepine plus betahistine group also did better than betahistine alone group.…”
Section: Betahistine Mesilatementioning
confidence: 84%